Dynamics of defect-loaded grain boundary under shear deformation in alpha iron. (5th January 2018) - Yang, L; Zhou, H L; Liu, H; Gao, F; Zu, X T; Peng, S M; Long, X G; Zhou, X S
Abstract: Two symmetric tilt grain boundaries (GBs) (Σ3⟨110⟩{112} and Σ11⟨110⟩{332}) in alpha iron were performed to investigate the dynamics of defect-loaded GBs under shear deformation. The results show that the loaded self-interstitial atoms (SIAs) reduce the critical stress of the coupled GB motion in the Σ3 GB, but increase the critical stress in the Σ11 GB. The loaded SIAs in the Σ3 GB easily form ⟨111⟩ clusters and remain in the bulk when the GB moves away. However, the SIAs move along with the Σ11 GB and combine with the vacancies in the bulk, leading to the defect self-healing. The helium (He) atoms loaded into the GBs significantly affect the coupled GB motion. Once He clusters emit interstitials, the Σ11 GB carries those interstitials away but the Σ3 does not. The loaded He atoms reduce the critical stress of the Σ3 GB, but increase the critical stress of the Σ11 GB.